Improved Ability to Analyze Short Stories with Discovery Learning Model - Niki Agustina (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2018)
This article discusses the improvement of the effectiveness of learning to analyze the short story by using discovery learning model. In addition, also discussed the increased interest of students in learning Research conducted using Classroom Action Research methods as much as three cycles. Data collection was done by observation technique, questionnaire, and cycle test. Target of this research is student of class VII-F of Negeri 3 Mande Junior High School year teaching 2016-2017 as many as 33 student. The results showed an increase; (1) II began not too nervous, and on the third cycle of the class is conducive; (2) student interest in literary learning increased in cycle I active students only a small part the effectiveness of learning increases in the first cycle of class is still groomed, the cycle, in cycle II half of active students and in cycle III almost all students active; (3) result of student learning in analyzing character and characterization and background of short story increase in cycle I with average value of student equal to 32,32, at cycle II reach 64,73, and at cycle III reach 85,15. It is concluded that learning using discovery learning model can improve the effectiveness of learning, can increase student’s interest in learning, and can improve student’s ability in analyzing character and character and characteristic and background in the short story in class VII Negeri 3 Mande Junior High School.Keywords: short story, and discovery learning model